K08 1993–2013: Two Decades of Predictive HD Testing at the Medical Genetics Service of the University Of Genoa. (17th September 2014) - Mandich, P; Lamp, M; Gulli, R; Iacometti, A; Marchese, R; Gotta, F; Abbruzzese, G; Ferrandes, G
Abstract : Background: A protocol for predictive testing (PT) has been applied, at the Medical Genetics Service, University of Genoa, since 1987. The geneticist and the psychologist are present together during the entire counselling process; this approach reflects the integration of competence and the holistic consideration of the applicant. Aims: To evaluate the features of applicants for predictive testing, their motivations and the outcomes of the counselling protocol. Methods: Retrospective analysis of the clinical charts of applicants; compilation of an ad hoc questionnaire by applicants. Results: A total of 294 persons (women 55.1%) applied for PT (1993–2013). About half of the applicants (57.1%) completed the protocol and 38.1% of them had a positive test result. At follow-up no catastrophic reactions were reported. Although more women applied for PT, the percentage of those who completed the protocol was significantly higher among men, 68.5% vs. 54.2% (p = 0.015). This trend was never reported in literature. Thirty two applicants presented neurological or psychiatric symptoms which could be associated to HD. The mean age of these subjects was significantly higher than that of asymptomatic persons: 41.5 vs. 34.5 years, respectively (p = 0.001). A modified protocol was built up to allow "symptomatic" applicants to take the test when it was considered useful to achieve disease awareness and for coping with the disease. Conclusions: Most applicants' features were overlapping with those previously described. However, our cohort is different for some features that may be related to both the population's differences (Italy vs other countries) and the protocol used. In addition, in our experience, the co-partnership of Genetics and Psychology is an effective method to take care of applicants during the protocol and to prevent operators' compassion fatigue.